Antibody response of infants to cell surface-exposed outer membrane proteins of Haemophilus influenzae type b after systemic Haemophilus disease. - Gulig, P A (1982)
The immune response of nine infants with Haemophilus influenzae type b meningitis was examined by using a radioimmunoprecipitation procedure designed to detect antibodies directed against cell surface-exposed outer membrane proteins of this pathogen. Using intrinsically or extrinsically radiolabeled intact H. influenzae type b cells with acute- and convalescent-phase human sera in this radioimmunoprecipitation system, we found that all of the infants produced an antibody response directed against several different H. influenzae type b outer membrane proteins. Anti-H. influenzae type b outer membrane protein antibodies present in convalescent sera, but not found in acute sera, were directed against cell surface-exposed H. influenzae type b outer membrane proteins. In contrast, both acute and convalescent sera contained antibody activity directed against numerous H. influenzae type b outer membrane proteins whose antigenic determinants were apparently inaccessible to antibody on intact H. influenzae type b cells. The ability of infants to develop an antibody response to cell surface-exposed, antibody-accessible H. influenzae type b outer membrane proteins indicates that these proteins may have vaccinogenic potential.